Role of IMRT/VMAT-Based Dose and Volume Parameters in Predicting 5-Year Local Control and Survival in Nasopharyngeal Cancer Patients - Iacovelli, Nicola Alessandro; Cicchetti, Alessandro; Cavallo, Anna; Alfieri, Salvatore; Locati, Laura; Ivaldi, Eliana; Ingargiola, Rossana; Romanello, Domenico A.; Bossi, Paolo; Cavalieri, Stefano; Tenconi, Chiara; Meroni, Silvia; et al. (Frontiers in Oncology, 2020)
To look into the relationship between intensity-modulated-radiotherapy (IMRT)-based dose-volume parameters and 5-year outcome for a consecutive series of non-metastatic nasopharyngeal cancer (NPC) patients (pts) treated in a single Institution in a non-endemic area in order to identify potential prognostic factors. A retrospective analysis of consecutive non-metastatic NPC pts treated curatively with IMRT or Volumetric Modulated Arc Therapy (VMAT) and chemotherapy (CHT) between 2004 and 2014 was conducted. One patient was in stage I (0.7%), 24 pts (17.5%) were in stage II, 38 pts (27.7%) in stage III, 29 pts (21.2%) in stage IVA and 45 pts (32.8%) in stage IVB. Five pts (3.6%) received RT alone. Of the remaining 132 pts (96.4%) 30 patients (21.9%) received CHT concomitant to RT and 102 patients (74.4%) were treated with induction CHT followed by RT-CHT. IMRT was given with standard fractionation at a total dose of 70 Gy. Clinical outcomes investigated in the study were local control (LC), disease-free survival (DFS) and overall survival (OS). Kaplan-Meier (KM) analysis was performed for the outcomes considering dose and coverage parameters, staging, RT technique. Overall, 137 pts were eligible for this retrospective analysis. With a median follow up of 70 months (range 12-143) actuarial rates at 5 years were: LC 90.4%, DFS 77.2% and OS 82.8%. For this preliminary study T stage was dichotomized as T1,T2,T3 vs T4. At 5 years the group T1-T2-T3 reported a LC of 93%, a DFS of 79% and a OS of 88%, whereas T4 pts reported LC, DFS and OS respectively of 56%, 50% and 78%. Pts with V95%>95.5% had better LC (p=0.006). Pts with D99%>63.8 Gy had better LC (p=0.034) and OS (p=0.005). The threshold value of 43.2 cc of GTVT was prognostic for LC (p=0.016). To predict the risk of local recurrence at 5 years we constructed a nomogram which combined GTVT with D99% relative to HRPTV. We demonstrated the prognostic value of some dose-volume parameters, although in a retrospective series, potentially useful to improve planning procedure. In addition, for the first time in a non-endemic area, a threshold value of GTVT, prognostic for LC, has been confirmed.